Geological Model for Khasib Formation of East Baghdad Field Southern Area - Jameel, Layth A.; Kadhim, Fadhil S.; Al-Sudani, Hussein Ilaibi (Journal of Petroleum Research and Studies, 2020)
Geological model construction is an important phase of reservoir study as the production capacity of a reservoir depends on its structural and petrophysical characteristics. The economic benefit of the reservoir is evaluated by estimating the formation petrophysical properties and calculating the oil reserves. East Baghdad southern area field is a newly developing oil field in the middle region of Iraq, where Khasib formation is its main reservoir. The aim of this study is to estimate the petrophysical properties and determine the pay units of the formation under study and the initial oil in place. Sequential Gaussian Simulation was used here to distribute the petrophysical properties as the statistical method and volumetric method was used to calculate the oil in place. The results show that the main reservoir units of the formation are K2 and K3 units, and the estimated oil reserves equal to 2179 mmSTB (346.43 million cubic meters).